Experimentally Induced Pulpal Lesion and Substance P Expression: Effect of Ketoprofen—A Preliminary Study. (29th February 2016) - Abbate, Gian Marco; Sacerdote, Paola; Amodeo, Giada; Mangano, Alessandro; Levrini, Luca
Abstract : Objectives. To evaluate substance P (SP) and the effect of ketoprofen administration, a nonsteroidal anti-inflammatory drug (NSAID), on SP in the pulp of upper third molars with experimentally induced pulpal lesion. Materials and Methods. A sample of 20 young systemically healthy adults of both sexes, nonsmokers, with a healthy upper third molar to extract for orthodontic purposes, was selected. Prior to the procedure, an inflammatory process was generated by mechanical exposure of the pulp. After 15 minutes, the pulp was collected using a sterile barbed broach. SP levels were determined by using a commercially available enzyme immunoassay (ELISA) kit. The subjects were randomly divided into two groups: group 1 received a dose of ketoprofen 30 minutes prior to the experimental procedure. The subjects of group 2 did not receive any kind of drug administration. The patients were asked to complete a diary on the postoperative pain. Results. No statistically significant difference could be detected in SP expression between the two groups. In group 1, pain manifestation was significantly delayed in comparison with group 2. Conclusions. Preventive administration of ketoprofen did not significantly affect the pulpal levels of SP but resulted in a significantly postponed manifestation of pain after extraction.